Copolymerization of carbon monoxide and styrene catalyzed by resin-supported palladium polymer (eXPRESS Polymer Letters)
Polyketone was prepared by the copolymerization of carbon monoxide (CO) and styrene (ST) catalyzed by o-phenylenediamine resin-supported palladium acetate. Effects of each catalytic system component such as 2,2’-bipyridine, 1,4-quinone and p-toluene-sulphonate on the copolymerization were investigated. The resin-supported catalyst and the copolymerization product were characterized by infrared spectroscopy (IR), differential scanning calorimetry (DSC), thermogravimetry (TG), X-ray photoelectron spectroscopy (XPS), Scanning Electron Microscopy (SEM). Results indicated that the resin-supported catalyst has excellent catalytic property. Furthermore, partial catalytic activity was maintained after the catalyst was used for five times.